International perspectives on the implementation of reproductive carrier screening. (29th November 2019) - Delatycki, Martin B.; Alkuraya, Fowzan; Archibald, Alison; Castellani, Carlo; Cornel, Martina; Grody, Wayne W.; Henneman, Lidewij; Ioannides, Adonis S.; Kirk, Edwin; Laing, Nigel; Lucassen, Anneke; Massie, John; et al.
Abstract: Reproductive carrier screening started in some countries in the 1970s for hemoglobinopathies and Tay‐Sachs disease. Cystic fibrosis carrier screening became possible in the late 1980s and with technical advances, screening of an ever increasing number of genes has become possible. The goal of carrier screening is to inform people about their risk of having children with autosomal recessive and X‐linked recessive disorders, to allow for informed decision making about reproductive options. The consequence may be a decrease in the birth prevalence of these conditions, which has occurred in several countries for some conditions. Different programs target different groups (high school, premarital, couples before conception, couples attending fertility clinics, and pregnant women) as does the governance structure (public health initiative and user pays). Ancestry‐based offers of screening are being replaced by expanded carrier screening panels with multiple genes that is independent of ancestry. This review describes screening in Australia, Cyprus, Israel, Italy, Malaysia, the Netherlands, Saudi Arabia, the United Kingdom, and the United States. It provides an insight into the enormous variability in how reproductive carrier screening is offered across the globe. This largely relates to geographical variation in carrier frequencies of genetic conditions and local health care, financial, cultural, and religious factors.